The reflective processes of principals as an engine of school change. Issue 2 (4th March 2022) - Cappelletti, Graciela; Sajon, Mariana Paz
ABSTRACT: Systematic reflection is understood as a paradigm that is a key component for processes of school change. Reflection includes knowledge, beliefs and experiences of teachers that are reconstructed and used as inputs to rethink their practices. This article presents the results of an investigation carried out in the period 2018–2019. It was proposed to investigate the reflective practice of secondary school principals who go through processes of school change. The research question was: What do school principals who are going through a process of change reflect on? We analyzed the narratives presented by school principals, organized in a portfolio that recovers the processes of each of the schools. The results provide knowledge about school principals as agents of change and the link between innovation or school change and reflection. It identifies a leadership that corresponds to high levels of reflection and is a key factor in going through the processes of school change. Leadership appears as a task that is shaped according to the needs of the school community, so a relationship is established between school leading and innovation processes. Thus, leadership is legitimized as a place for research during practice and construction of knowledge about the processes of school change.